Turning biennial into biannual harvest: Long-term assessment of Arabica coffee–macadamia intercropping and irrigation synergism by biological and economic indices - Soratto, Rogério P. [UNESP]; Perdoná, Marcos J.; Parecido, Renan J. [UNESP]; Pinotti, Raquel N.; Gitari, Harun I. (Wiley, 2022)
Intercropping that involves coffee (Coffee arabica L.) and macadamia (Macadamia integrifolia Maiden & Betche) can achieve the complementarity between component crops aiming at better use of natural resources, hence resulting in optimum crop production. However, there is no detailed information in the scientific literature about the biological and economic efficiency of coffee–macadamia intercropping. In this work, we evaluated the productivity and economic performance of Arabica coffee–macadamia intercropping under rainfed and irrigated conditions for 13 years (2006–2018) in São Paulo state, southeastern Brazil. In addition, some biological, economic, and competition indices were used to understand the complementarity of companion crops under the intercropping system. Irrigation significantly increased coffee (21%–40%) and macadamia (33%–44%) yields. Despite the greater values of aggressivity and dominance indices of macadamia over coffee crop have been calculated in the rainfed regime, intercropping with macadamia reduced more strongly coffee yield under irrigation. The higher values of land equivalent ratio (LER), land equivalent coefficient (LEC), percentage yield difference (PYD), income equivalent ratio (IER), and relative net return index (RNRI) indicated relatively higher benefits of intercropping under rainfed regime than under irrigation. The intercropping systems were more productive than monocrops, reaching 215% more yield, 3.2-fold more gross income under rainfed conditions. The synergy of the combined use of irrigation and intercropping technologies decreased the payback period and the highest values of coffee equivalent yield (CEY) and monetary advantage index (MAI) under irrigation indicated a cumulative effect on the profitability. Here, for the first time, we demonstrated the complementarity between Arabica coffee and macadamia under the intercropping system, at least up to 13 years after planting of the crops, and suggest that it may be a viable option to optimize the use of resources, food production, and ecosystem services, making agricultural profitability more sustainable and stable.